LITERASI KEUANGAN, EDUKASI, DAN LINGKUNGAN SOSIAL SEBAGAI DETERMINAN MINAT INVESTASI MASYARAKAT DI PASAR MODAL DENGAN MODERASI PEKERJAAN - MOHAMMAD SOFYAN; ANDRI MUHARIZAL PUTRA; MUNAWAR ASIKIN; ABDUL GOFUR; DANNY INDRIANTO (JURNAL AKUNTANSI DAN KEUANGAN, 2025)
This study aims to identify and analyze the influence of Financial Literacy, Investment Education, Social Environment, and Employment on Investment Interest using the Structural Equation Modeling (SEM) approach. The validity and reliability of the constructs were assessed through indicators such as Cronbach’s Alpha, Composite Reliability, and Average Variance Extracted (AVE), while discriminant validity was tested using the Fornell-Larcker Criterion and the Heterotrait-Monotrait Ratio (HTMT). The results indicate that Social Environment is the most dominant factor influencing investment interest, followed by Investment Education and Financial Literacy, each showing statistically significant effects. Conversely, the Employment variable and its interactions with other constructs did not exhibit significant influence. The model demonstrates strong predictive power, with an R-square value of 0.787, indicating that nearly 79% of the variance in investment interest can be explained by the constructs within the model. These findings highlight the importance of social and educational approaches in shaping investment behavior and offer practical implications for developing more effective financial literacy and investment education strategies.